Forward problem solving for non-invasive electrical resistance tomography system - Abdul Wahab, Yasmin; Abdul Rahim, Ruzairi; Pusppanathan, Jaysuman; Rahiman, Mohd Hafiz Fazalul; Leow, Pei Ling; Ridzuan Aw, Suzanna; Abdul Rahim, Herlina (Malaysian Society for Computed Tomography & Imaging Technology (MyCT), 2018)
This paper aims to provide a forward problem solving for non-invasive electrical resistance tomography. A finite element model (FEM) using COMSOL Multiphysics is implemented for generating the sensitivity map for ERT system. Later, a masking data for a better sensitivity map was done to optimize the map. As a result, the sensitivity map can be used later for reconstructing the image of the medium of interest.